A New Dual Circularly Polarized Feed Employing a Dielectric Cylinder-Loaded Circular Waveguide Open End Fed by Crossed Dipoles - Jae-Hoon Bang; Soon-Woo Choi; Jae-Woo Noh; Joo-Young Lim; Dong-Hyun Kim; Dae-Oh Kim; Bierng-Chearl Ahn (International Journal of Antennas and Propagation)
This paper presents a new dual circularly polarized feed that provides good axial ratio over wide angles and low cross-polarized radiation in backward direction. A circular waveguide open end is fed with two orthogonally polarized waves in phase quadrature by a pair of printed crossed dipoles and a compact connectorized quadrature hybrid coupler. The waveguide aperture is loaded with a dielectric cylinder to reduce the cross-polarization beyond 90 degrees off the boresight. The fabricated feed has, at 5.5 GHz, 6.33-dBic copolarized gain, 3-dB beamwidth of 106°, 10-dB beamwidth of 195°, 3-dB axial ratio beamwidth of 215°, maximum cross-polarized gain of −21.4 dBic, and 27-dB port isolation. The reflection coefficient of the feed is less than −10 dB at 4.99–6.09 GHz.